TerminoCLIL: a terminology-based approach to CLIL - Moreira Silva, Manuel (2021)
Considering the new European educational context deriving from the Bologna Process, the urgency of improving university students’ Foreign Languages (FL) competences and the unsatisfactory results of present-day methodological approaches to FL teaching and learning, it seems that the ground is, as Morgado and Coelho (2012) state, ripe for new perspectives in this area. CLIL appears as one of these approaches – more content oriented, more able to meaningfully integrate language and content and to lead to the desired FL proficiency and pluricultural learning outcomes. It is also based on a new paradigm: that of the language user, rather than the language learner (Moore and Dooly 2010).